A critical appraisal of audiometers manufactured in India - Tlruvenkatachari (Journal of All India Institute of Speech and Hearing, 1970)
In  1962  Bharath  Electronics  Limited  manufactured  the  first  audiometer in India.    It was demonstrated in Jaipur in the same year.    The latest model which differs from the earlier one in only one feature is being used at  the  All India Institute of Speech and Hearing.    The feature that has been added to this model  is the Normal/Reverse switch  used to present continuous tone or to in- terrupt the same. An attempt is made in this article to express the views of a user.